Малогабаритный стационарный пирометр с повышенным температурным разрешением - Akhijezer, A. M. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A design option for a compact stationary pyrometer with enhanced temperature resolution is proposed. As a modulator, a moving pyroelectric sensor is suggested, which reduces infrared radiation absorption due to the absence of a light guide. To decrease thermal noise and the noise of the input amplifier stage, thermal stabilization of the optical part of the pyrometer at a reduced temperature is applied. To improve stability and measurement accuracy, calibration is performed using two reference levels of infrared radiation.